Journalism as activism recoding media power - Russell, Adrienne (Cambridge, UK ; Malden, MA Polity Press, 2016)
"Journalism as Activism explores the ways everyday meaning and the material realities of media power are tied to the communication tools we have access to, the architectures of digital space we navigate, and our ability to master and modify our media environments."--Publisher's description.
Introduction -- Networks -- Tools: prototyping change -- Practice -- Power.
Prof. Ma. Theresa Tabada (Recommending faculty) - Bookfair2017
Includes bibliographical references and index.
Keywords: Journalism -- Political aspects; Press and politics; Citizen journalism -- Political aspects; Digital media -- Political aspects